Development and Utilization of Functional Kompetitive Allele-Specific PCR Markers for Key Genes Underpinning Fiber Length and Strength in Gossypium hirsutum L. - Li, Lihua; Sun, Zhengwen; Zhang, Yan; Ke, Huifeng; Yang, Jun; Li, Zhikun; Wu, Liqiang; Zhang, Guiyin; Wang, Xingfen; Ma, Zhiying (Frontiers in Plant Science, 2022)
Fiber length (FL) and fiber strength (FS) are the important indicators of fiber quality in cotton. Longer and stronger fibers are preferred for manufacturing finer yarns in the textile industry. Functional markers (FMs) designed from polymorphic sites within gene sequences attributing to phenotypic variation are highly efficient when used for marker assisted selection (MAS) in breeding superior varieties with longer FL and higher FS. The aims of this study were to develop functional markers via kompetitive allele-specific PCR (KASP) assays and to validate the efficacy of the FMs for allele discrimination and the potential value in practice application. We used four SNP markers and 360 cotton accessions, and found that two FMs, D11_24030087 and A07_72204443, could effectively differentiate accessions of different genotypes with higher consistency to phenotype. The appeared frequency of varieties harbored Hap2 (elite alleles G and T) with longer FL (> the mean of accessions with non-elite allele, 28.50 mm) and higher FS (> the mean of accessions with non-elite allele, 29.06 cN•tex-1) was 100% or 72.7%, respectively, which was obviously higher than that of varieties harbored only a single elite allele (G or T, 77.9% or 61.9%), suggesting a favorable haplotype for selecting varieties with superior FL and FS. These FMs could be valuable for the high-throughput selection of superior materials by providing genotypic information in cotton breeding programs.